Implementasi Keselamatan dan Kesehatan Kerja di Puskesmas: Studi Kasus di Kabupaten Pekalongan - Fitria Qotrotun Nada; Hanifa Maher Denny; Yuliani Setyaningsih (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2020)
Background: The regulation of “PERMENKES NO. 52/2018” stipulates that a health care service institution is requied to implement the occupational health program for its employees.Methods: This study utilized qualitative methods to explain the implementation of occupational safety and health in a health care setting. The main informants were 5 people and triangulantions were 2 people. The instruments in this study used indepth interview guidelines and observation sheets. The study site was conducted in pekalongan district.Results: The result indicated that Delegation or SK, Resources , Waste Treatment, Incident Reporting, Occupational Disease Reporting, Health care and Emergency Response accordance with the regulation. However, OSH Policy, Annual Work Plan, The level of compliance with OSH implementation and The Socialization of SOP didn’t accordance with the regulation.Conclusion: Based on the results of research on the implementation of 10 indicators of success OSH Primary Health Care, there are 4 variables (OSH Policy, Annual Work Plan, The level of compliance with OSH implementation and The Socialization of SOP) must be improved.